Airway clearance techniques and use of mucoactive agents for adult critically ill patients with acute respiratory failure: a qualitative study exploring UK physiotherapy practice. (September 2020) - Connolly, Bronwen; Barclay, Matthew; Blackwood, Bronagh; Bradley, Judy; Anand, Rohan; Borthwick, Mark; Chikhani, Marc; Dark, Paul; Shyamsundar, Murali; Warburton, John; McAuley, Daniel F.; O'Neill, Brenda
Abstract: Objectives: To explore and describe current UK physiotherapy practice relating to airway clearance techniques and mucoactive agents in critically ill adult patients with acute respiratory failure in the intensive care unit. Design: A descriptive, qualitative study using focus group interviews. Focus groups were audio-recorded, independently transcribed, and data analysed thematically. Participants Senior, experienced physiotherapists, clinically active in critical care. Results: Fifteen physiotherapists participated in four interview sessions. Five themes emerged describing airway clearance techniques: 'Repertoire of airway clearance techniques', 'Staffing and skillset', 'Commencing respiratory physiotherapy', 'Technique selection', and 'Determining effectiveness' were themes related to airway clearance techniques. Five themes were also identified in relation to mucoactive agents: 'Use in clinical practice', 'Decision to commence', 'Selection of agent', 'Stopping mucoactive agents', and 'Determining effectiveness'. A summary of key features of standard practice was developed. Conclusions: Standard UK physiotherapy practice of airway clearance techniques is variable, but patient-centred and targeted to individual need, with adjunctive use of mucoactive agents to enhance and optimise patient management if required. Based on this study, key features of airway clearance techniques have been summarised to help capture standard care, which could be used in future trials involving ACT as part of usual care.